The Efficiency Effects of Discrete Tax Rate Changes Without Lump-Sum Taxes and Transfers - Neil Bruce (Queen's University, Department of Economics, 1990)
An exact expression for the normalized change in utility resulting from discrete changes in tax rates on economic activities is derived using certain linearity assumptions in preferences. This expression is used to consider alternative ways of identifying the resulting efficiency cost (or excess burden) when lump-sum taxes and transfers are assumed to be unavailable to compensate for revenue changes. Benchmark tax structures other than lump-sum taxation, specifically Ramsey optimal and uniform tax structures, are used to identify the efficiency cost of revenue neutral tax changes. The results are used to explain and extend various known results on the efficiency effects of such tax changes as well as to make an efficiency case for avoiding arbitrary departures from uniformity even when lump-sum taxes are infeasible. Finally, the theoretical shortcomings of considering revenue neutral tax changes are considered and an alternative methodology is introduced.
Keywords: 330